Trends in indirect liver function marker testing in Wales from 2000 to 2017 and their association with age and sex: an observational study - Joe West; Joanne R Morling; Trevor Alexander Hill; Colin John Crooks (BMJ Open Gastroenterology)
Objective If non-invasive markers of liver fibrosis were recorded frequently enough in clinical practice, it might be feasible to use them for opportunistic community screening for liver disease. We aimed to determine their current pattern of usage in the national primary care population in Wales.Design Using the Secure Anonymised Information Linkage (SAIL) Databank at Swansea University (2000–2017), we quantified the frequency of common liver blood tests (aspartate aminotransferase (AST), alanine aminotransferase (ALT), platelet count and albumin) used in fibrosis marker algorithms. We examined measurement variation by age and sex.Results During the 18-year study period, there were 2 145 178 adult patients with at least one blood test available for analysis. Over the study period, the percentage of SAIL patients receiving an ALT test in each year increased from 2% to 33%, with platelet count and albumin measurement increasing by a similar factor. AST testing, although initially rising, had decreased to 1% by the end of the study. AST and ALT values varied by age and sex, particularly in males with the upper normal range of ALT values decreasing rapidly from 90 U/L at age 30 to 45 U/L by age 80.Conclusion The reduction in AST testing to only 1% of the adult population limits the use of many non-invasive liver marker algorithms. To enable widespread screening, alternative algorithms for liver fibrosis that do not depend on AST should be developed. Liver fibrosis markers should be modified to include age-specific and sex-specific normal ranges.